KURIKULUM PENDIDIKAN AGAMA ISLAM BERBASIS LEARNING ANALYTICS UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI PERGURUAN TINGGI - Nailul Muna; Nurhafifah; Amiruddin; Sulaiman (STKIP Subang, 2026)
The development of digital technology has brought significant changes to the higher education system, including the evaluation process of the Islamic Religious Education (PAI) curriculum. Curriculum evaluation, which has focused primarily on measuring final learning outcomes, is deemed incapable of providing a comprehensive picture of the effectiveness of the learning process. Therefore, a more adaptive and data-driven evaluation approach is needed. This article aims to examine the development of a learning analytics-based Islamic Religious Education curriculum evaluation model as an effort to improve the quality of learning in higher education. The method used is a literature review, analyzing various literature related to curriculum evaluation, Islamic religious education, and learning analytics. The results of the study indicate that integrating learning analytics into curriculum evaluation allows for more accurate collection, measurement, analysis, and interpretation of learning data, thus providing a basis for decision-making in curriculum development. The developed evaluation model encompasses aspects of input, process, output, and learning outcomes, supported by data on student activity on digital platforms. Therefore, the implementation of a learning analytics-based evaluation model can improve learning effectiveness, the achievement of graduate learning outcomes, and the quality of Islamic religious education in higher education.